2022
DOI: 10.1021/acsanm.1c03987
|View full text |Cite
|
Sign up to set email alerts
|

Fe2O3 Nanocatalysts Supported on Zeolite-Y for the Selective Synthesis of C2 Di-Indolyl Indolones and Isatins

Abstract: Iron-oxide (Fe 2 O 3 ) nanoparticles in the dimension of ∼2.3 nm supported on zeolite-Y appeared as an excellent, reusable heterogeneous catalyst for the chromatography-free selective synthesis of 2,2-di(3-indolyl)-3-indolones, a C2-trimerized product. The zeolite-Y-supported Fe-oxide nanocatalyst showed the catalytic activity better than the Pd-and Au-based catalysts in the synthesis of C2 di-indolyl indolones under the prevailing reaction conditions. Besides, this low-cost catalyst displayed the ability to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 68 publications
4
27
0
Order By: Relevance
“…At the same time, our previous study and various other studies reported that iron oxide can activate PMS. 6,15 Iron oxides are comparatively more environment friendly, highly abundant and hence cost-effective. Therefore, instead of using CuO, freshly prepared Fe 2 O 3 was used as the catalyst for the same reaction under the same reaction conditions.…”
Section: Nmr (Esi) †mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, our previous study and various other studies reported that iron oxide can activate PMS. 6,15 Iron oxides are comparatively more environment friendly, highly abundant and hence cost-effective. Therefore, instead of using CuO, freshly prepared Fe 2 O 3 was used as the catalyst for the same reaction under the same reaction conditions.…”
Section: Nmr (Esi) †mentioning
confidence: 99%
“…5 At the same time, CuO is also known to activate peroxymonosulfate (PMS) which is used as an oxidant in the synthesis of C2/C3-trimerized indoles. 6 However, no literature is available on the application of the CuO-PMS system for the synthesis of 3,3′-BIMs through the dehydrogenation of CH 3 OH or C 2 H 5 OH. So in this work, an attempt was made to use the CuO-PMS system as an alternative to the known Ir and Ru catalysts for similar reactions.…”
mentioning
confidence: 99%
“…Several studies have been reported on the trimerization of indoles using homogeneous and heterogeneous catalysts (Scheme 1A‐I) [2] . However, these catalytic systems inevitably require organic and inorganic oxidants such as tert ‐butyl hydroperoxide (TBHP) [2a–c] and oxone, [2d,e] respectively, which produce large amounts of waste. From the atom efficiency and environmental viewpoint, molecular oxygen (O 2 ) has been considered an ideal oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…10 During our recent studies on an iron oxide nanocatalyst supported on Na + -zeolite-Y, Fe 2 O 3 -Y was found to be a reusable and effective heterogeneous catalyst for the selective C-2 trimerization of indoles. 11 As these iron (Fe) catalysts are much cheaper and abundant in nature, so a similar Fe 2 O 3 catalyst is explored herewith to overcome the problems associated with the C(1)–H functionalization of 2-naphthol and its derivatives. Herein, we designed a Fe 2 O 3 nanocatalyst supported on potassium exchanged zeolite-Y (Fe 2 O 3 -KY).…”
mentioning
confidence: 99%
“…However, the yield was significantly lower than in the case of our previously reported Fe 2 O 3 nanocatalyst supported on zeolite-NaY, halloysite nanotubes (HNT), alumina (Al 2 O 3 ), or silica (SiO 2 ). 11,16 Previous studies have reported that in such reactions, particularly those involving π-systems, the cation–π interactions play a significant role in the product formation. 9 We have also reported that during the oxidative coupling of 2-naphthols, the cation–π interactions played a vital role.…”
mentioning
confidence: 99%